Comparison Analysis of Product Research Based on Similar Kitchenware Products Between Shopee and Traditional Market (Case Study: Sumber Rejeki Shop) (Future Science, 2021)
The Covid-19 pandemic has had a major impact on transactions and economic activities for online sellers and traditional markets. Sellers need a new strategy to determine products that have the potential to be sold, one of which is through product research. Product research is a strategy for sellers to find information about a product that customers need and reach the target market by comparing the competitive price, quality, and product variants. Not only online shops but also traditional market sellers must also know product research to be able to survive the Covid-19 pandemic. Based on these problems, community service programs were held by inviting seller partners from the Gresik city market to provide briefing and assistance on product research. The results of the product research show that the kitchenware products sold by Sumber Rejeki shops as seller partners in the program have similarities with competitor products sold in the Shopee marketplace. There were five products analyzed, namely plastic plates, rattan plates, egg molds, bakwan mold, and wooden vegetable cutters. The product descriptions listed by seller partners in the Shopee marketplace have disadvantages, they are not describing product quality, name product titles too short, set prices that are less competitive with competitors, and lack efforts to promote products. Therefore, the results of this product research are expected to be able to improve the strategy of sellers to determine product details and variants, prices, product quality against competitors